DESIGNING CLEAN PRODUCTION OF TOFU PROCESSING INDUSTRY IN UD. SUMBER URIP PELAIHARI - Jaka Darma Jaya; Luthfina Ariyani; Hadijah Hadijah (Jurnal Agroindustri, 2018)
Tofu is an Indonesian traditional food which basically made from soybean. Tofu production process yields both solid and liquid wastes. If these are not handled properly, they may cause environmental contamination. Therefore, clean production planning needs to be conducted in order to bringout an environmental friendly industry for increasing productivity, increasing efficiency of raw materials and reducing wastes. This research was conducted at the tofu processing industry UD. Sumber Urip by collecting data through field observation, interview, questionnaire filling and 3 (three) stages of quick scan method which consists of identifing the production process of tofu based on the concept of clean production through the mass balance, analysing the alternative clean production improvements, observating and giving recommendations on waste utilization. The result shows that the tofu production process with clean production through the mass balance produced 210 kg dregs of tofu and 2.115,51 kg total liquid wastes. The research also proposes some alternative improvements of clean production as the implementation of good housekeeping principle, modification of funnel principle grinding, utilization of  personal protective equipment, and implementation of recovery and reduce principle. On the other hand the wastes generated from the tofu production process may be reproduced in to tempe gembus, animal feed, organic fertilizer, and biogas.